Evolução e Morfofuncionalidade da Mesopleura de Bethylidae (hymenoptera: Chrysidoidea) - Brito, Chirlei Dias de (2021)
The mesopleuron of Bethylidae has many characters that are constantly used in alpha-taxonomic and cladistic studies. However, the understanding of these structures is still not clear and the works that analyzed them do so in a superficial and independent way, which often implies in propositions of mistaken homologies and confusion of terms. In the first chapter, a morphological study and literature review were made in order to standardize the terms used in the mesopleuron. Our study resulted in an anatomic glossary with 49 terms that presented a large number of synonyms and polysemies. The glossary standardizes the terms used in the Bethylidae mesopleuron and in other Hymenoptera groups, which will facilitate hypotheses of primary homology in comparative biology. In the second chapter, we described the general mesopleural anatomy of Bethylidae, matching external and internal (muscles and apodemes) structures, and then proposed primary homologies. After surveying the characters and their respective states, we selected ten of them and reconstructed the ancestral state of the main mesopleural structures using the maximum-likelihood method. For this, we built a phylogeny of Bethylidae using the genes COI and 28s for the maximum-likelihood and Bayesian inference methods. Our analysis yielded similar results, but we chose Bayesian inference to perform the character evolution analyses as it presented better clade support. In both phylogenies, Bethylidae and all subfamilies were recovered as monophyletic with high clade support values. The study of mesopleural anatomy allowed exploring and discussing characters and their present states not only in Bethylidae, but also in Hymenoptera; muscle data made inferences about the biology of some genera of Epyrinae and female Pristocerinae; and the reconstruction of the ancestral state showed many characters that arose independently in Bethylidae subfamilies.